Direct laser metal deposition additive manufacturing of Inconel 718 superalloy: Statistical modelling and optimization by design of experiments. (December 2021) - Moradi, Mahmoud; Hasani, Arman; Pourmand, Zeynab; Lawrence, Jonathan
Highlights: Direct Laser Metal Deposition Additive Manufacturing of Inconel 718 Superalloy is investigated by DOE. Parameters varied for DOE analysis are scanning speed, powder feed rate, scanning strategies. Geometrical dimensions, layer stability, microstructure, and the micro-hardness are selected as output parameters. Abstract: Direct laser metal deposition (DLMD) technique is used for additive manufacturing (AM) of Inconel 718 Ni-based superalloy using full factorial design. A 1 kW fiber laser is applied with a coupled coaxial nozzle head. Laser scanning speed (2.5–5.0 mm/s), powder feed rate (17.94–28.52 g/min), and scanning strategies (Unidirectional, Bidirectional) were considered as the input process variables while geometrical dimensions (height, width average), standard deviation of microhardness, and the stability of additively manufactured walls were determined as process responses. The influence of process parameters on the responses variations were studied by analysis of variance (ANOVA). Results indicated that low scanning speed and high powder feed rate caused to increase in height and average width of AM samples. Due to microstructural phases, the microhardness changes have an unstable trend. Results show that a stable wall was obtained in low scanning speed and unidirectional scanning pattern. In order to achieve a desired condition for the DLMD additive manufacturing process, optimization was conducted based on the applied statistical analyses. The scanning speed of 2.5 mm/s, the powder feed rate of 28.52 g/min, and unidirectional scanning pattern were identified as the optimum conditions.